Partisipasi Penyuluh, Petani Pemandu Dan Petani Pada Program P3tip di Desa Bahal Gajah Kecamatan Sidamanik Kabupaten Simalungun - Nadeak, Nita Dermawati; Tety, Ermi; ', Rosnita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
ABSTRACT The study is titled "Participation Extension Agent, guide Farmers and Farmers on P3TIP Program at Desa Bahal Gajah Kecamatan Sidamanik Kabupaten Simalungun". This study used a survey method. Aim 1) Knowing participation of extension workers, guide farmers and growers ((penanam dan tumbuhan)perkebunan, petani, investor, kultivator, petani, peternak) in the program P3TIP and 2) Knowing what are the problems faced by extension, guide farmers and growers to participate in the program P3TIP. The method used in the study is a survey method. Bahal Gajah village elections conducted by purposive sampling the achievements obtained the first example in the activity levels of the North Sumatera seed paddy rice. Samples were taken 25 farmers using purposive sampling (farmers active in P3TIP program), and also it was taken 1 extension and 1 farmer guides, so that the total sample was 27 people. Analysis of the participation of the respondents using a Likert Scale Scale's Summated. The results of the study illustrate the extension of participation are in the category of "High" with a score of 2.3, the farmer guides categorized as "High" with a score of 1.78, and farmers are also categorized as "High" with a score of 3.87 on P3TIP program. The problem faced by the extension that is participating in the planning as an educator and consultant, still have limited ability to P3TIP program. Problems faced by farmers guide is to facilitate farmers in developing partnerships to companies is still limited and the problems faced by farmers, namely the implementation of farmers meeting with investigators to discuss P3TIP. Keywords: Participation, Agricultural Extension, Farmers and Empowerment